Urethane resin composition, laminate, and shaped object

The urethane resin composition with a visible light-responsive photocatalyst, featuring rutile titanium oxide and a divalent copper compound, addresses the need for simple and effective antiviral materials by imparting durable antiviral properties to surfaces and objects.

JP7653053B2Active Publication Date: 2025-03-28DIC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021002647
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-29
Filing Date
2021-01-12
Publication Date
2025-03-28
Estimated Expiration
2041-01-12

AI Technical Summary

Technical Problem

There is a need for materials and products that can impart antiviral properties in a simple and cost-effective manner, especially for items frequently touched by many people, as conventional antibacterial and antiviral agents often irritate the skin and lose effectiveness over time.

Method used

A urethane resin composition containing a visible light-responsive photocatalyst, specifically a metal compound supported on titanium oxide, is used to create a laminate and shaped objects with antiviral properties. The composition includes rutile titanium oxide and a divalent copper compound, which enhances photocatalytic activity and antiviral performance.

Benefits of technology

The urethane resin composition effectively imparts antiviral properties to films and shaped objects, maintaining performance over time and reducing skin irritation, thus addressing the limitations of conventional antiviral agents.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a urethane resin composition that can impart antiviral properties, and a laminate and a molding with antiviral properties imparted thereto.SOLUTION: The present invention discloses a urethane resin composition containing a visible light-responsive photocatalyst. Preferably, the visible light-responsive photocatalyst should be a titanium oxide (a) having a metal compound supported thereon. Preferably, the titanium oxide (a) should include a rutile titanium oxide (a1). Preferably, the metal compound should be a divalent copper compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a urethane resin composition that can be imparted with antiviral properties by containing a visible light responsive photocatalyst, and to a laminate and a shaped object to which antiviral properties have been imparted. [Background technology]

[0002] In recent years, the spread of various viruses and bacteria, including the new coronavirus, has led to an increased demand throughout society for products with antibacterial and antiviral properties. There is a particularly high demand for these products in places that are touched by many people and for items that are used frequently, but because it takes time and money to change all existing equipment and items to ones that have antibacterial and antiviral properties, there is a demand for products that can impart these properties in a simple manner.

[0003] Conventionally used antibacterial and antiviral agents include various alcohols, quaternary ammonium salt compounds, silver-based compounds, and copper-based compounds, but these do not fully meet market requirements, such as skin irritation and reduced antibacterial and antiviral properties over time.

[0004] In contrast, photocatalysts that use titanium oxide are less irritating to the human body and maintain their antibacterial and antiviral properties for a long period of time, so there are high expectations for their practical use (see Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-166705 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a urethane resin composition capable of imparting antiviral properties, and a laminate and a shaped article to which antiviral properties have been imparted. [Means for solving the problem]

[0007] The present invention provides a urethane resin composition capable of being imparted with antiviral properties by containing a visible light responsive photocatalyst, and synthetic leather and a shaped article imparted with antiviral properties by containing the urethane resin composition.

[0008] [1] A urethane resin composition comprising a visible light responsive photocatalyst. [2] The urethane resin composition according to [1], wherein the visible light responsive photocatalyst is a metal compound supported on titanium oxide (a). [3] The urethane resin composition according to [2], wherein the titanium oxide (a) comprises rutile titanium oxide (a1). [4] The urethane resin composition according to [2] or [3], wherein the metal compound is a divalent copper compound. [5] The urethane resin composition according to any one of [1] to [4], wherein the content of the visible light responsive photocatalyst is 0.3 parts by mass or more and 67 parts by mass or less, based on 100 parts by mass of the resin solid content of the urethane resin composition. [6] A laminate comprising a fibrous base material and a surface layer formed on at least one surface of the fibrous base material from the urethane resin composition according to any one of [1] to [5]. [7] The laminate according to [6], further comprising a surface treatment layer formed on the surface of the skin layer using a surface treatment agent. [8] The laminate according to [6] or [7], wherein the form of the fibrous substrate is one selected from the group consisting of knitted fabrics, woven fabrics, and nonwoven fabrics. [9] A shaped object made of the urethane resin composition according to any one of [1] to [4] above.

[10] The object according to [9], characterized in that it is produced by fused deposition modeling. Effect of the Invention

[0009] The urethane resin composition of the present invention can provide a coating and a shaped article having antiviral properties. The laminate and the shaped article having the coating have antiviral properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The urethane resin composition of the present invention contains a urethane resin and a visible light responsive photocatalyst.

[0011] The visible light responsive photocatalyst may be, for example, a composition containing titanium oxide (a). In terms of obtaining even more excellent antiviral properties, a composition in which a metal compound is supported on titanium oxide (a) is preferred.

[0012] As the titanium oxide (a), for example, rutile type titanium oxide (a1), anatase type titanium oxide, brookite type titanium oxide, etc. can be used. These titanium oxides may be used alone or in combination of two or more. Among these, it is preferable to include rutile type titanium oxide (a1) because it has excellent photocatalytic activity in the visible light region.

[0013] The content of the rutile type titanium oxide (a1) (rutilated ratio) is preferably 15 mol % or more, more preferably 50 mol % or more, and even more preferably 90 mol % or more, based on the total titanium oxide (a), in order to obtain even more excellent antiviral properties in bright places and dark places and visible light responsiveness.

[0014] Generally, the liquid phase method and the gas phase method are known as the manufacturing method of the titanium oxide (a). The liquid phase method is a method in which titanium oxide is obtained by hydrolyzing or neutralizing titanyl sulfate obtained from a liquid in which raw ore such as ilmenite ore is dissolved. The gas phase method is a method in which titanium oxide is obtained by a gas phase reaction between titanium tetrachloride obtained by chlorinating raw ore such as rutile ore and oxygen. In addition, a method for distinguishing between titanium oxides manufactured by both methods includes analyzing the impurities. Titanium oxide manufactured by the liquid phase method contains zirconium, niobium, etc. derived from impurities in ilmenite ore in the product. In contrast, the gas phase method has a process of purifying titanium tetrachloride and removing impurities, so that these impurities are hardly contained in titanium oxide.

[0015] Although titanium oxide produced by the gas phase method has the advantage of being able to produce uniform particle diameters, it is believed that secondary aggregates are difficult to produce, and therefore the apparent specific surface area is high, which increases the viscosity of the mixed liquid during the reaction process. In contrast, titanium oxide (a) produced by the liquid phase method is believed to produce gentle secondary aggregates in the firing process, and has low coagulation power compared to the specific surface area (BET value) caused by the primary particles, making it possible to suppress the viscosity of the mixed liquid. For the above reasons, titanium oxide (a) produced by the liquid phase method is preferred because it can further improve the productivity of the self-cleaning agent.

[0016] The BET specific surface area of ​​the titanium oxide (a) is preferably 1 to 200 m, since it provides even more excellent antiviral properties and visible light responsiveness. 2 / g is preferable, and 3 to 100m 2 / g is more preferable, and 4 to 70m 2 / g is more preferable, and 8 to 50m 2 The range of 7.5 to 9.5 m / g is more preferable since the productivity of the antiviral agent can be further increased. 2The BET specific surface area of ​​the rutile-type titanium oxide (a1) is preferably in the range of 1 / g. The method for measuring the BET specific surface area of ​​the rutile-type titanium oxide (a1) will be described in the Examples below.

[0017] The primary particle diameter of the titanium oxide (a) is preferably in the range of 0.01 to 0.5 μm, more preferably in the range of 0.06 to 0.35 μm, in order to obtain even better antiviral properties and visible light responsiveness. The primary particle diameter of the titanium oxide (a) is measured by a method in which a transmission electron microscope (TEM) is used to directly measure the size of the primary particles from an electron microscope photograph. Specifically, the minor axis diameter and major axis diameter of each primary particle of titanium oxide are measured, and the average is taken as the particle diameter of the primary particles. Next, the volume (weight) of each particle is calculated for 100 or more titanium oxide particles by approximating it to a cube of the calculated particle diameter, and the volume average particle diameter is taken as the average primary particle diameter.

[0018] In addition, as the visible light responsive photocatalyst, it is preferable to use a metal compound supported on titanium oxide (a), since this further improves the photocatalytic activity in the visible light region and makes it easier to exhibit appropriate activity under practical indoor lighting.

[0019] As the metal compound, for example, a copper compound, an iron compound, a tungsten compound, etc. can be used. Among these, a copper compound is preferred, and a divalent copper compound is more preferred, in that it provides even more excellent antibacterial and antiviral properties. A known method can be used to support the metal compound on the titanium oxide (a).

[0020] Next, the most preferred embodiment, that is, the method for supporting a divalent copper compound on titanium oxide (a), will be described.

[0021] An example of a method for supporting a divalent copper compound on the titanium oxide (a) is a method having a mixing step (i) of titanium oxide (a) including rutile-type titanium oxide (a1), a divalent copper compound raw material (b), water (c), and an alkaline substance (d).

[0022] The concentration of the titanium oxide (a) in the mixing step (i) is preferably in the range of 3 to 40% by mass. In the present invention, when titanium oxide (a) produced by a liquid phase method is used, the mixing step can be carried out with good handling even if the concentration of the titanium oxide (a) is increased, and specifically, the mixing step can be carried out well even if the concentration of the titanium oxide (a) is in the range of more than 25% by mass to 40% by mass or less.

[0023] As the divalent copper compound raw material (b), for example, an inorganic divalent copper compound, an organic divalent copper compound, etc. can be used.

[0024] Examples of the divalent copper inorganic compound that can be used include inorganic acid salts of divalent copper such as copper sulfate, copper nitrate, copper iodate, copper perchlorate, copper oxalate, copper tetraborate, ammonium copper sulfate, copper amidosulfate, ammonium copper chloride, copper pyrophosphate, and copper carbonate; divalent copper halides such as copper chloride, copper fluoride, and copper bromide; copper oxide, copper sulfide, azurite, malachite, and copper azide. These compounds may be used alone or in combination of two or more.

[0025] Examples of the divalent copper organic compound include copper formate, copper acetate, copper propionate, copper butyrate, copper valerate, copper caproate, copper enanthate, copper caprylate, copper pelargonate, copper caprate, copper myristic acid, copper palmitate, copper margarate, copper stearate, copper oleate, copper lactate, copper malate, copper citrate, copper benzoate, copper phthalate, copper isophthalate, copper terephthalate, copper salicylate, copper mellitic acid, copper oxalate, copper malonate, copper succinate, copper glutarate, copper adipate, copper fumarate, and glycol. Examples of compounds that can be used include copper glycerate, copper gluconate, copper tartrate, copper acetylacetone, copper ethylacetoacetate, copper isovalerate, copper β-resorcylate, copper diacetoacetate, copper formylsuccinate, copper salicylamine, copper bis(2-ethylhexanoate), copper sebacate, copper naphthenate, copper oxine, copper acetylacetone, copper ethylacetoacetate, copper trifluoromethanesulfonate, copper phthalocyanine, copper ethoxide, copper isopropoxide, copper methoxide, and copper dimethyldithiocarbamate. These compounds may be used alone or in combination of two or more.

[0026] As the divalent copper compound raw material (b), among those mentioned above, it is preferable to use one represented by the following general formula (1). CuX2(1) (In formula (1), X is a halogen atom, CH3COO, NO3, or (SO4) 1 / 2 (Indicates

[0027] X in the above formula (1) is more preferably a halogen atom, and further preferably a chlorine atom.

[0028] The amount of the divalent copper compound raw material (b) used in the mixing step (i) is preferably in the range of 0.01 to 20 parts by mass, more preferably in the range of 0.1 to 15 parts by mass, and even more preferably in the range of 0.3 to 10 parts by mass, relative to 100 parts by mass of the titanium oxide (a).

[0029] The water (c) is a solvent in the mixing step (i), and is preferably water alone, but may contain other solvents as necessary. Examples of the other solvents that can be used include alcohol solvents such as methanol, ethanol, 1-propanol, 2-propanol, and 1-butanol; ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone; dimethylformamide, tetrahydrofuran, and the like. These solvents may be used alone or in combination of two or more.

[0030] As the alkaline substance (d), for example, sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, triethylamine, trimethylamine, ammonia, a basic surfactant, etc. can be used, and it is preferable to use sodium hydroxide.

[0031] The alkaline substance (d) is preferably added as a solution in order to facilitate control of the reaction. The concentration of the alkaline solution to be added is preferably in the range of 0.1 to 5 mol / L, more preferably in the range of 0.3 to 4 mol / L, and even more preferably in the range of 0.5 to 3 mol / L.

[0032] In the mixing step (i), the titanium oxide (a), the divalent copper compound raw material (b), water (c), and the alkaline substance (d) may be mixed, for example, by first mixing the titanium oxide (a) with the water (c) and stirring as necessary, then mixing and stirring the divalent copper compound raw material (b), and then adding and stirring the alkaline substance (d). By this mixing step (i), the divalent copper compound derived from the divalent copper compound raw material (b) is supported on the titanium oxide (a).

[0033] The total stirring time in the mixing step (i) is, for example, 5 to 120 minutes, and preferably 10 to 60 minutes. The temperature during the mixing step (i) is, for example, in the range of room temperature to 70°C.

[0034] In order to favorably support the divalent copper compound on the titanium oxide (a), the titanium oxide (a), the divalent copper compound raw material (b), and water (c) are mixed and stirred, and then the alkaline substance (d) is mixed and stirred. The pH of the mixture thus obtained is preferably in the range of 8 to 11, and more preferably in the range of 9.0 to 10.5.

[0035] After the mixing step (i) is completed, the mixture can be separated as a solid content. Examples of the method for the separation include filtration, sedimentation, centrifugation, evaporation and drying, and filtration is preferred. The separated solid content may then be washed with water, crushed, classified, etc., as necessary.

[0036] After obtaining the solid content, it is preferable to heat treat the solid content in order to more firmly bind the divalent copper compound derived from the divalent copper compound raw material (b) supported on the titanium oxide (a). The heat treatment temperature is preferably in the range of 150 to 600° C., more preferably in the range of 250 to 450° C. The heat treatment time is preferably 1 to 10 hours, more preferably 2 to 5 hours.

[0037] By the above method, a titanium oxide composition containing titanium oxide in which a divalent copper compound is supported on titanium oxide (a) can be obtained. The amount of the divalent copper compound supported on the titanium oxide (a) is preferably in the range of 0.01 to 20 parts by mass per 100 parts by mass of titanium oxide (a) from the viewpoint of photocatalytic activity including antiviral activity. The amount of the divalent copper compound supported can be adjusted by the amount of the divalent copper compound raw material (b) used in the mixing step (i).

[0038] The content of the visible light responsive photocatalyst in the urethane resin composition is not particularly limited within the range in which the effects of the present invention can be obtained, but when the resin solid content of the urethane resin composition is 100 parts by mass, the lower limit is usually 0.3 parts by mass or more, preferably 3.3 parts by mass or more, more preferably 10 parts by mass or more, and the upper limit is usually 67 parts by mass or less, preferably 50 parts by mass or less, more preferably 33 parts by mass or less. Any combination of these upper and lower limits may be used. The content of the visible light responsive photocatalyst in the urethane resin composition is usually 0.3 parts by mass or more and 67 parts by mass or less, preferably 3.3 parts by mass or more and 50 parts by mass or less, more preferably 10 parts by mass or more and 33 parts by mass or less, when the resin solid content of the urethane resin composition is 100 parts by mass.

[0039] Examples of the urethane resin used in the present invention include polyether-based urethane resin, polycarbonate-based urethane resin, polyester-based urethane resin, resin and modified products thereof, and either thermosetting urethane resin or thermoplastic polyurethane resin can be used. Among these, polyether-based urethane resin is suitable when flexibility is required for sports shoes and clothing applications. Polycarbonate-based urethane resin is suitable when long-term durability is required for applications such as furniture and vehicles. The molecular weight of the urethane resin varies depending on the application and required performance, but may be appropriately selected from the number average molecular weight range of 5,000 to 50,000, preferably 5,000 to 15,000.

[0040] Examples of the polyol component that is a raw material of the urethane resin include polyoxyethylene glycol, polyoxypropylene glycol, polyoxytetramethylene glycol, polyethylene adipate, polypropylene adipate, polyoxytetraethylene adipate, etc. These polyol components can be used alone or in combination of two or more kinds.

[0041] Examples of the isocyanate component that is a raw material of the urethane resin include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, 3,3'-dichloro-4,4'-biphenylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-tetrahydronaphthalene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, etc. These polyisocyanates can be used alone or in combination of two or more kinds.

[0042] A crosslinking agent can be added to the urethane resin composition of the present invention as necessary. The crosslinking agent is not particularly limited as long as it can crosslink with the urethane resin used in the present invention. Examples of such crosslinking agents include compounds having two or more functional groups in one molecule that can react with functional groups such as active hydrogen atoms in the urethane resin, or cyclic compounds that can react with functional groups such as active hydrogen atoms in the urethane resin by opening the ring to form bonds and crosslink the urethane resin. Specific examples include epoxy compounds, aziridine compounds, carbodiimide compounds, polyisocyanate compounds, oxazoline compounds, melamine formamide compounds, and urea methylol compounds. Among these, polyisocyanate compounds are preferred. These crosslinking agents can be used alone or in combination of two or more.

[0043] An organic solvent may be added to the urethane resin composition of the present invention to impart coatability. The organic solvent is not particularly limited as long as it dissolves the urethane resin. Examples of such organic solvents include organic solvents such as N,N-dimethylformamide (hereinafter abbreviated as DMF). In addition, in order to improve the drying property after application of the resin solution, methanol, ethanol, isopropyl alcohol, toluene, methyl ethyl ketone, ethyl acetate, cyclohexanone, ethyl cellosolve, methyl cellosolve, propylene glycol methyl ether, propylene glycol methyl ether acetate, N-methylpyrrolidone, etc. can be used. Among these, cyclohexanone, ethyl acetate, methyl ethyl ketone, ethanol, methanol, isopropyl alcohol, etc., which have a boiling point of less than 100°C, are particularly preferred. These solvents used to improve the drying property can be used alone or in combination of two or more.

[0044] The total blend amount of the organic solvent and the solvent used to improve drying properties as necessary is preferably in the range of 5 to 60% by mass so that the solid content concentration of the resin composition is 5 to 60% by mass.

[0045] The urethane resin composition of the present invention can be suitably used not only for the surface layer, adhesive layer and intermediate layer of a fibrous substrate, but also for a surface treatment layer on the surface of the surface layer.

[0046] If necessary, various additives such as crosslinking accelerators, colorants such as organic pigments, flame retardants and antioxidants, and resins other than urethane resins may also be added to the urethane resin composition of the present invention.

[0047] Furthermore, when manufacturing a shaped object by various molding methods, it is preferable to use a thermoplastic urethane resin. These thermoplastic polyurethanes are resins obtained by polymerizing a polyol and a polyisocyanate in the presence of a chain extender.

[0048] The polyol used as the raw material of the thermoplastic polyurethane resin is not particularly limited, and conventionally known polyols can be used. Examples of these polyols include high molecular weight polyols such as polyester polyols, polyether polyols, polycarbonate polyols, and polylactone polyols. These polyols may be used alone or in combination of two or more.

[0049] The average molecular weight (number average molecular weight) of the polyol used as a raw material for the thermoplastic polyurethane resin may be appropriately selected from the range of preferably 500 to 5,000, more preferably 700 to 4,000.

[0050] Specific examples of polyols used as raw materials for the thermoplastic urethane resin include polyols obtained by dealcoholization reaction between low molecular weight polyols such as polytetramethylene glycol, polyethylene glycol, polypropylene glycol, polyethylene adipate, polybutylene adipate, polyhexamethylene adipate, ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, nonanediol, and 1,4-cyclohexanedimethanol and carbonate compounds such as diethylene carbonate, dipropylene carbonate, and diphenyl carbonate. These polyol components can be used alone or in combination of two or more kinds.

[0051] The polyisocyanate used as a raw material for the thermoplastic urethane resin is not particularly limited as long as it has two or more isocyanate groups, and conventionally known polyisocyanates can be used. For example, aliphatic isocyanates such as 1,6-hexamethylene diisocyanate (HDI), 2,2,4-trimethylhexamethylene diisocyanate, methylene diisocyanate, isopropylene diisocyanate, lysine diisocyanate, lysine diisocyanate methyl ester, and 1,5-octylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate (IPDI), norbornene diisocyanate, and the like can be used. isocyanate, hydrogenated tolylene diisocyanate, methylcyclohexane diisocyanate, isopropylidene bis (4-cyclohexyl isocyanate), alicyclic isocyanates such as dimer acid diisocyanate, 2,4- or 2,6-tolylene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthylene diisocyanate, p- or m-xylylene diisocyanate (XDI), Examples of the isocyanates include aromatic isocyanates such as lysine diisocyanate, p-phenylene diisocyanate, diphenyl ether diisocyanate, diphenyl sulfone diisocyanate, dianisidine diisocyanate, and tetramethyl-m-xylylene diisocyanate, triphenylmethane triisocyanate, triisocyanate phenyl thiophosphate, polymethylene polyphenylene polyisocyanate (polymeric MDI), isocyanurate modified products and biuret modified products which are trimers of HDI and TDI, and polyols obtained by dealcoholization reaction of low molecular weight polyols such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, nonanediol, and 1,4-cyclohexanedimethanol with carbonate compounds such as diethylene carbonate, dipropylene carbonate, and diphenyl carbonate. These polyisocyanates can be used alone or in combination of two or more.

[0052] The chain extender used as a raw material for the thermoplastic urethane resin is not particularly limited, and conventionally known ones can be used. As the chain extender, for example, conventionally known polyhydric alcohols and amines can be used, but low molecular weight polyols having 2 to 10 carbon atoms are preferred. Examples of these low molecular weight polyols include aliphatic polyols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 2-methylpentanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, octanediol, nonanediol, decanediol, trimethylpropane, and glycerin, alicyclic polyols such as cyclohexanediol and cyclohexanedimethanol, and aromatic polyols such as bishydroxyethoxybenzene and xylene glycol. These chain extenders can be used alone or in combination of two or more.

[0053] When a thermoplastic polyurethane is used in the present invention, additives such as a silane coupling agent, a filler, a thixotropy imparting agent, a tackifier, a wax, a plasticizer, a heat stabilizer, an antioxidant, an ultraviolet absorber, a light resistance stabilizer, a filler, a fiber-based reinforcing material, a pigment, a fluorescent brightening agent, a foaming agent, a thermoplastic resin, a thermosetting resin, a dye, an electrical conductivity imparting agent, an antistatic agent, a moisture permeability improving agent, a water repellent agent, an oil repellent agent, a hollow foam, a compound containing crystal water, a flame retardant, a water absorbing agent, a moisture absorbing agent, a deodorant, an antibacterial agent, an antifungal agent, an antiblocking agent, a hydrolysis inhibitor, an organic water-soluble compound, or an inorganic water-soluble compound may be blended therein, as necessary.

[0054] Next, specific embodiments in which the urethane resin composition is used will be described.

[0055] The urethane resin composition of the present invention can be used as a coating agent for fibrous substrates. The coating agent is an agent for obtaining a film formed on the surface of a substrate, and includes the concept of a surface treatment agent. By coating the surface of a fibrous substrate with a urethane resin composition, a laminate having a surface layer with excellent antiviral properties can be obtained. By further surface-treating the surface of the surface layer with a urethane resin composition, a laminate having a surface layer and a surface treatment layer on the surface of the fibrous substrate can be obtained, and the antiviral properties can be further improved.

[0056] Examples of materials for the fibrous base material include natural fibers (plant and animal fibers) such as cotton, linen, and silk; and chemical fibers such as polyester, nylon, acrylic, and polyurethane.

[0057] Examples of the form of the fibrous base material include knitted fabrics, woven fabrics, nonwoven fabrics, and the like.

[0058] Specific examples of articles having the laminate of the present invention include synthetic leather, artificial leather, natural leather, automobile interior seats using polyvinyl chloride (PVC) leather, sports shoes, clothing, furniture, thermoplastic olefin (TPO) leather, dashboards, instrument panels, and the like.

[0059] The laminate of the present invention can be produced by a known dry film-forming method, for example, the following method.

[0060] The resin composition for the surface layer is applied onto the release paper with a doctor knife and then dried. Next, the resin composition for the adhesive layer is applied onto the dried coating film of the surface layer with a doctor knife and then pre-dried. Then, the nonwoven fabric is laminated and then dried. After aging, the release paper is peeled off to obtain a laminate.

[0061] The thickness of the layer made of the urethane resin composition is preferably in the range of, for example, 0.1 to 100 μm.

[0062] The urethane resin composition of the present invention can be made into a shaped object by various shaping methods. As these shaping methods, a three-dimensional shaping method such as fused deposition modeling, and well-known shaping methods such as vacuum molding and injection molding can be used, but shaping by a three-dimensional shaping method such as fused deposition modeling is preferable because the visible light responsive photocatalyst is uniformly distributed on the shaped object and the effects of the present invention can be suitably obtained.

[0063] When a three-dimensional modeling method such as fused deposition modeling is selected for producing the object of the present invention, the urethane resin composition may be in the form of a powder, pellet, filament, etc., and may be appropriately selected depending on the three-dimensional modeling device to be used.

[0064] Examples of objects formed by the three-dimensional modeling method include mechanical industrial parts such as belts, tubes, hoses, electric wire coating materials, cable coating materials, waterproof hoses, gears, casters, packings, and wind turbines for wind power generation; bumpers, side moldings, tail lamp seals, snow chains, ball joint seals, constant velocity joint boots, bellows, spring cover materials, ABS cables, ABS cable plugs, instrument panel skins, gear knobs, console boxes, door seal covers, seat materials, and car parts such as knobs; various seats, air mattresses, synthetic leather, films and sheets such as protective films, shoe soles, watch bands, camera grips, animal ear tags, smartphone cases, tablet cases, keyboard protective covers, and everyday items such as decorative items; medical products such as heart valves, bypass devices, artificial ventricles, dialysis tubes, thin films, connectors, catheters, medical tubes, and pacemaker insulators; building materials such as interior and exterior materials; and sporting goods such as skis, snowboards, surfboards, and rackets, and the like, and the like can be used in a wide range of fields both indoors and outdoors. EXAMPLES

[0065] The present invention will now be described more specifically with reference to examples. [Photocatalyst preparation example 1] (1) Titanium dioxide a) Crystalline rutile titanium dioxide b) Manufacturing method: Liquid phase method (sulfuric acid method) c) Physical properties ·BET specific surface area: 9.0m 2 / g Rutile rate: 95.4% ·Primary particle size: 0.18μm

[0066] [Method for measuring the BET specific surface area of ​​titanium dioxide (a)] The specific surface area was measured (BET single point method) using a fully automatic BET specific surface area measuring device "MacSORB HM model-1208" manufactured by Mountech Co., Ltd.

[0067] [Method for measuring the rutilated ratio of titanium dioxide (a)] Using an X-ray diffractometer "XRD-6100" manufactured by Shimadzu Corporation, the peak height ratio corresponding to rutile crystals was calculated from the peak heights corresponding to the entire titanium oxide crystals (rutile, brookite, and anatase types).

[0068] [Method for measuring the primary particle size of titanium dioxide (a)] The size of the primary particles was measured directly from electron micrographs using a transmission electron microscope (TEM). Specifically, the minor and major axis diameters of each titanium oxide primary particle were measured, and the average was taken as the particle diameter of the primary particles. Next, the volume (weight) of each of 100 or more titanium oxide particles was calculated by approximating it to the cube of the calculated particle diameter, and the volume-average particle diameter was taken as the average primary particle diameter.

[0069] (2) Manufacturing process a) Mixing process (reaction process) 600 parts by mass of the titanium oxide, 8 parts by mass of copper(II) chloride dihydrate, and 900 parts by mass of water were mixed in a stainless steel container. The mixture was then stirred with a stirrer ("Robomix" manufactured by Tokushu Kika Kogyo Co., Ltd.), and a 1 mol / L aqueous solution of sodium hydroxide was added dropwise until the pH of the mixture reached 10. b) Dehydration process The mixture was filtered under reduced pressure using qualitative filter paper (5C) to separate the solid matter from the mixture, and then washed with ion-exchanged water. The washed solid matter was then dried at 120°C for 12 hours to remove moisture. After drying, a powdered titanium oxide composition was obtained using a mill (Iwatani Sangyo Co., Ltd.'s "Miller"). c) Heat treatment process The mixture was heat-treated at 450° C. for 3 hours in the presence of oxygen using a precision incubator (DH650 manufactured by Yamato Scientific Co., Ltd.) to obtain a titanium oxide composition containing titanium oxide carrying a divalent copper compound.

[0070] [Photocatalyst preparation example 2] (1) Titanium dioxide a) Crystalline rutile titanium dioxide b) Manufacturing method: Gas phase method c) Physical properties ·BET specific surface area: 13m 2 / g Rutilated ratio: 95.6% ·Primary particle size: 0.15μm

[0071] A titanium oxide composition was obtained in the same manner as in Preparation Example 1, except that the type of titanium oxide was changed to the above titanium oxide and the amount of water used was changed from 900 parts by mass to 4,000 parts by mass.

[0072] [Method for measuring the amount of divalent copper compound supported on titanium oxide (a)] The titanium oxide compositions obtained in Preparation Examples were completely dissolved in a hydrofluoric acid solution, and the extract was analyzed by an ICP emission spectrometer to quantify the amount of divalent copper compound supported on titanium oxide (a) (amount of divalent copper compound supported (parts by mass) / titanium oxide (a) (parts by mass)). As a result, in both Preparation Examples 1 and 2, the amount of copper ions was 0.5 parts by mass per 100 parts by mass of titanium oxide.

[0073] [Preparation of urethane resin composition] <Materials for urethane resin composition> Crisbon NB-130 (polyether-polyester type urethane resin solution that does not yellow easily (DIC Corporation), one-component urethane resin, resin solids: 30% by weight, DMF: 70% by weight) Dilac White L-6725 (colorant (DIC), rutile pigment-grade titanium dioxide; 50%, DMF; 40%, urethane resin solids; 10%) Crisbon TA-265 (polyether-based yellowing-resistant urethane resin solution (DIC), two-component urethane resin, resin solids: 65% by weight, DMF: 35% by weight) Burnock DN-950 (polyisocyanate compound (DIC Corporation, resin solids: 75% by weight, ethyl acetate: 25% by weight) · Crisbon Accel T-81E: Crosslinking accelerator (DIC)

[0074] <Composition of urethane resin composition> A resin composition A for a surface layer was obtained by mixing the following materials in a homomixer. (1) CRISBON NB-130 100 parts by weight (2) DMF 40 parts by mass (3) Dilac White L-6725 15 parts by weight (4) Preparation Example 1 or Preparation Example 2 0.5 to 15 parts by weight

[0075] A resin composition B for a surface layer was obtained by mixing the following materials in a homomixer. (1) CRISBON NB-130 100 parts by weight (2) DMF 40 parts by mass (3) Dilac White L-6725 15 parts by weight

[0076] A resin composition for adhesive layers was obtained by mixing the following materials in a homomixer. (1) 100 parts by weight of CRISBON TA-265 (2) DMF 20 parts by mass (3)MEK 20 parts by mass (4) Burnock DN-950 12 parts by weight (5) 3 parts by weight of CRISBON Axel T-81E

[0077] Surface treatment resin composition A was obtained by mixing the following materials in a homomixer. (1) CRISBON NB-130 100 parts by weight (2) DMF 100 parts by mass (3)MEK 100 parts by mass (4) Preparation Example 1 or Preparation Example 2 5 parts by weight

[0078] Surface treatment resin composition B was obtained by mixing the following materials in a homomixer. (1) CRISBON NB-130 100 parts by weight (2) DMF 100 parts by mass (3)MEK 100 parts by mass

[0079] [How to prepare evaluation samples] An artificial leather for evaluation was prepared by the following dry film formation method. On a release paper (product name "Asahi Release AR-191" manufactured by Asahi Roll Co., Ltd.), the resin composition A or B for the surface layer was applied with a doctor knife to a thickness of 150 μm (film thickness when dried is about 30 μm), and then dried with hot air at 120 ° C for 2 minutes. Next, on the dried coating film of the surface layer, the resin composition for the adhesive layer was applied with a doctor knife to a thickness of 150 μm (film thickness when dried is about 50 μm), and then pre-dried with hot air at 70 ° C for 1 minute. Furthermore, the pre-dried adhesive layer was attached to a nonwoven fabric, and then dried with hot air at 120 ° C for 2 minutes. After that, it was aged at 70 ° C for 12 hours, and the release paper was peeled off to prepare an artificial leather for evaluation. When further surface treatment was performed, the surface treatment resin composition A or B was applied to a thickness of 20 μm (7 μm thick when dried) using a gravure coater, and then dried with hot air at 80° C. for 2 minutes.

[0080] [Method for evaluating antiviral activity] The artificial leather for evaluation obtained above was subjected to an anti-phage virus test (film adhesion method, see JIS R1756:2020).

[0081] 1) The light irradiation conditions were white fluorescent light with an N113 filter to cut out ultraviolet rays, and the illuminance was 1000 lux. 2) 100 μL of Qβ phage solution of a known concentration was dropped onto a 5 cm × 5 cm piece of artificial leather for evaluation, and then a 4 cm × 4 cm adhesive film was placed over it to prepare a sample for evaluation. 3) The sample was irradiated for 2 hours, recovered in SCDLP liquid, appropriately diluted, infected with E. coli, spread on an agar medium, and evaluated by counting the number of colonies after cultivation. Antiviral activity was evaluated by the degree of inactivation of Qβ phage, and an inactivation level of -2 to -5 was evaluated as having antiviral activity.

[0082] The degree of inactivation is the log(N / N0) value, which indicates the degree of reduction in the phage infectivity in a bright place. N is the infectivity (pfu / mm 2 ), N0 is the infectious titer of the inoculated phage (pfu / mm 2 ) Inactivation level 1 indicates that 90% of the virus has been inactivated, inactivation level 2 indicates that 99%, inactivation level 3 indicates that 99.9%, inactivation level 4 indicates that 99.99%, and inactivation level 5 indicates that 99.999% of the virus has been inactivated, indicating high antiviral activity.

[0083] <Example 1> Resin composition A for surface layer: Add 5 parts by mass of Preparation Example 1 No surface treatment (Evaluation result) Inactivity level: -3 → Antiviral

[0084] <Example 2> Resin composition A for surface layer: 15 parts by mass of Preparation Example 1 added No surface treatment (Evaluation result) Inactivity level: -5 → Antiviral

[0085] <Example 3> Resin composition A for surface layer: Add 5 parts by mass of Preparation Example 2 No surface treatment (Evaluation result) Inactivity level: -3 → Antiviral

[0086] <Example 4> Resin composition A for surface layer: 0.5 parts by mass of Preparation Example 1 added No surface treatment (Evaluation result) Inactivity level: -2 → Antiviral

[0087] <Example 5> Resin composition B for surface layer: Neither Preparation Example 1 nor Preparation Example 2 was added. Surface treatment agent included. Add 5 parts by mass of Preparation Example 1 to Surface Treatment Resin Composition A. (Evaluation result) Inactivity level: -3 → Antiviral

[0088] <Example 6> Resin composition B for surface layer: Neither Preparation Example 1 nor Preparation Example 2 was added. Surface treatment agent included. Add 5 parts by mass of Preparation Example 2 to Surface Treatment Resin Composition A. (Evaluation result) Inactivity level: -3 → Antiviral

[0089] <Example 7> Resin composition A for surface layer: Add 5 parts by mass of Preparation Example 1 Surface treatment agent included. Add 5 parts by mass of Preparation Example 1 to Surface Treatment Agent Composition A. (Evaluation result) Inactivity level: -4 → Antiviral

[0090] <Comparative Example 1> Resin composition B for surface layer: Neither Preparation Example 1 nor Preparation Example 2 was added. No surface treatment (Evaluation result) Inactivity level: -0.2 → No antiviral activity

[0091] <Comparative Example 2> Resin composition B for surface layer: Neither Preparation Example 1 nor Preparation Example 2 was added. Surface treatment resin composition B: Neither Preparation Example 1 nor Preparation Example 2 was added. (Evaluation result) Inactivity level: -0.2 → No antiviral activity

[0092] <Comparative Example 3> Resin composition A for surface layer: Add 5 parts by mass of Preparation Example 1 Surface treatment resin composition B: Neither Preparation Example 1 nor Preparation Example 2 was added. (Evaluation result) Inactivity level: -0.2 → No antiviral activity

[0093] [Manufacturing of urethane resin molded objects] Examples of the production of a shaped object using the urethane resin composition of the present invention will be described below.

[0094] [Preparation of urethane resin composition] <Materials for urethane resin composition> Pantex T-9290 (polycarbonate-based thermoplastic urethane (manufactured by DIC Covestro Polymers)), Irganox 1010 (phenol-based antioxidant (manufactured by BASF))

[0095] <Composition of urethane resin composition> Composition A for shaping was prepared by kneading the following raw materials by melt kneading extrusion to obtain filaments. (1) Pantex T-9290 100 parts by weight (2) Adjustment example 1 11 parts by mass (3) Irganox 1010 0.3 to 0.4 parts by weight

[0096] Composition B for shaping was prepared by kneading the following raw materials by melt kneading extrusion to obtain filaments. (1) Pantex T-9290 100 parts by weight (2) Adjustment example 1 25 parts by mass (3) Irganox 1010 0.3 to 0.4 parts by weight

[0097] [How to prepare evaluation samples] Preparation Example 1 An additive-free product (Pantex T-9290 100 parts by weight) and the above-mentioned shaped article compositions A and B were further processed into a filament shape by melt kneading extrusion to obtain a filament having a filament diameter of 2.85 mmφ.

[0098] The filament was subjected to fusion deposition modeling using a three-dimensional modeling device (manufactured by Ultimaker) to produce a model measuring 60 mm x 60 mm x 2 mm, which was then adjusted to a size of 50 mm x 50 mm x 2 mm to obtain a sample for evaluation.

[0099] [Method for evaluating antiviral activity] The evaluation samples obtained above were subjected to an antiviral test (see ISO21702 (JIS Z2801)).

[0100] 1) Preparation example 1 of evaluation sample 0.4 ml of virus liquid was dropped onto the additive-free product and onto the modeling composition A and B, and covered with a film measuring 40 mm x 40 mm. 2) Leave at 25℃ for 24 hours. 3) After leaving the test piece to stand, the virus on the test piece is washed and collected, and then the virus infectivity is measured.

[0101] The virus used in the virus test was influenza A virus (H3N2), and the percentage of virus reduction (virus reduction rate %) was calculated using the following formula. A virus reduction rate of 95% or more was evaluated as having antiviral activity. Formula) R=(Ut-At) / Ut×100 R: Virus reduction rate % Ut: Viral infectivity (PFU / cm) of additive-free sample after 24 hours of standing 2 ) average At: viral infectivity (PFU / cm) of compositions A and B after standing for 24 hours 2 ) average

[0102] <Comparative Example 4> Adjustment example 1 Additive-free product (Evaluation Results) Influenza A virus (H3N2); virus reduction rate 0% → no antiviral effect

[0103] <Example 8> Composition A for shaped objects (Evaluation Results) Influenza A virus (H3N2); virus reduction rate 97% → antiviral effect

[0104] <Example 9> Composition B for shaped objects (Evaluation Results) Influenza A virus (H3N2); Virus reduction rate of 99% → antiviral properties

Claims

1. A urethane resin composition comprising a visible light responsive photocatalyst, The visible light responsive photocatalyst is a titanium oxide including a rutile type titanium oxide having a divalent copper compound supported thereon, The urethane resin composition, wherein the visible light responsive photocatalyst is a visible light responsive photocatalyst obtained by mixing titanium oxide including rutile type titanium oxide, a divalent copper compound raw material, water and an alkaline substance.

2. The urethane resin composition according to claim 1, wherein the divalent copper compound raw material is a compound represented by CuX 2 (X is a halogen atom, CH 3 COO, NO 3 or (SO 4 ) 1 / 2 ).

3. A urethane resin composition according to claim 1 or 2, wherein the divalent copper compound raw material is used in an amount of 0.1 to 15 parts by mass per 100 parts by mass of the titanium oxide.

4. A urethane resin composition described in any of claims 1 to 3, wherein the alkaline substance is one or more selected from sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, triethylamine, trimethylamine, and ammonia.

5. The content of the visible light responsive photocatalyst is 0.3 parts by mass or more and 67 parts by mass or less when the resin solid content of the urethane resin composition is 100 parts by mass. The urethane resin composition according to any one of claims 1 to 4.

6. A laminate comprising a fibrous base material and a skin layer on at least one surface of the fibrous base material, A laminate, wherein the surface layer is formed from the urethane resin composition according to any one of claims 1 to 5.

7. A laminate comprising a fibrous base material, a skin layer on at least one surface of the fibrous base material, and a surface treatment layer on the skin layer, A laminate, wherein the surface-treated layer is formed from the urethane resin composition according to any one of claims 1 to 5.

8. 8. The laminate according to claim 6, wherein the fibrous substrate is in the form of one selected from the group consisting of nonwoven fabric, knitted fabric, and woven fabric.

9. A shaped object comprising the urethane resin composition according to any one of claims 1 to 4.

10. The object according to claim 9, which is formed by a fused deposition modeling process.

Citation Information

Patent Citations

  • Composite particle containing titanium dioxide and its application

    JP2006124267A

  • Virus inactivating agent

    JP2013166705A

  • Methods and systems for using thermoplastic polyurethanes in hot melt lamination and articles thereof

    JP2017505834A

  • Copper-and-titanium-containing composition and production method therefor

    WO2013094573A1

  • Decorative sheet and method for manufacturing same

    WO2017122737A1